The Role of Technology and Industry 4.0 in Enhancing Digital Connectivity, Local Economic Development, and Human Resource Quality in the Digital Era in Gorontalo City - Meilan Daud; Mohammad Zubair Hippy; Siti Rahmatia Machieu; Dian Rahayu Maku; Mustakim Mokoginta; Djunaida Kandow; Indriyati Lanangawa (International Journal of Economics, Business and Innovation Research, 2026)
The digital economic transformation and the implementation of Industry 4.0 have become a primary urgency in accelerating regional development, particularly in enhancing digital connectivity, local economic development, and the quality of human resources (HR) in the digital era. This study aims to analyze the role of technology and Industry 4.0 in driving digital-based economic progress in Gorontalo City and to evaluate its effectiveness in three main aspects: digital connectivity, local economy, and HR strengthening. Using a mixed-method approach with an explanatory design, data were collected through questionnaires, observations, documentation, and focus group discussions (FGD) from 20 respondents consisting of local government agencies (OPD), the public, and relevant stakeholders. The analysis was conducted using the Importance-Performance Analysis (IPA) method and the qualitative technique of the Miles & Huberman model. The results show that the impact of technology on the local economy and digital connectivity was deemed quite effective, although improvements are still needed, particularly in infrastructure and access equity. Meanwhile, the strengthening of HR and digital skills-based employment is still categorized as less effective and remains a top priority for improvement. Therefore, it is recommended that the government expand digital training, strengthen cross-sector partnerships, and promote inclusive policies to ensure that digital transformation progresses equitably and sustainably.